(3GdJhVjM Ydi CdajI GHf eGdcs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s
(3ChdgG (B:s
(3HGH GdJQNje GdJQNje ai GddZI JQbjb GdUhJ hJdjjfg s
(3BNQgG (B:s
(3Je hGdMeO ddg ceG gh Cgdg, hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hSde JSdjeG WjHG eHGQcG Edi jhe GdOjf, hGdMeO ddg QH GdYGdejf, hdG Mhd hdG bhI EdG HGddg GdYdj GdYXje s
(3GdfU jfbU cKjQG ef Chdgs
(3EP JYO GdfSNI LRkAG KGfkjG dLRA ZjQ eJhaQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B211s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B152s
Keywords: (3GdfMhs